2017
DOI: 10.1007/s00330-017-5151-y
|View full text |Cite
|
Sign up to set email alerts
|

Can dual-energy CT replace perfusion CT for the functional evaluation of advanced hepatocellular carcinoma?

Abstract: • Late-arterial iodine concentration is highly related to arterial BF and BV. • Portal iodine concentration mainly reflects tumour blood volume. • Dual-energy CT offers significantly decreased radiation dose compared with perfusion CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 27 publications
3
30
0
Order By: Relevance
“…For DECT, the three materials in the thorax most frequently analyzed are iodine, air, and soft tissue. A single contrast material–enhanced acquisition can supply both virtual nonenhanced images and contrast‐enhanced CT data, which may obviate the additional acquisition of true nonenhanced CT scans 11,20 . In the study by Reiter et al, 21 the size of pulmonary nodules ≤3 cm were evaluated by DECT.…”
Section: Discussionmentioning
confidence: 99%
“…For DECT, the three materials in the thorax most frequently analyzed are iodine, air, and soft tissue. A single contrast material–enhanced acquisition can supply both virtual nonenhanced images and contrast‐enhanced CT data, which may obviate the additional acquisition of true nonenhanced CT scans 11,20 . In the study by Reiter et al, 21 the size of pulmonary nodules ≤3 cm were evaluated by DECT.…”
Section: Discussionmentioning
confidence: 99%
“…CT perfusion imaging clinical application has not been widely promoted because of the large radiation dose. Mule S, et al have shown arterial IC to be significantly related to both arterial blood flow and blood volume, confirming the ability of DECT to evaluate both morphological and perfusion changes 28 . Sonja Gordic, et al found strong intra-individual correlations between iodine density and arterial perfusion ( r = 0.75) 29 .…”
Section: Discussionmentioning
confidence: 74%
“…One study using 4-dimensional perfusion CT found that 5 out of 6 liver tumor lesions included in the study showed significant decreases in tumor perfusion compared with baseline one week after the onset of sorafenib treatment, which might support the hypothesis of vascular normalization after sorafenib treatment in that outlier case (77). However, Mule et al (78) questioned whether perfusion CT could be replaced by dual-energy CT for evaluating the response to sorafenib or radioembolization in patients with advanced HCC.…”
Section: Perfusion Imagingmentioning
confidence: 83%